PENGARUH PENETAPAN WAKTU HUJAN TERHADAP BESARNYA DEBIT BANJIR RENCANA - NEGARA, I D G JAYA; WIRADARMA, LALU WIRAHMAN; YASA, I WAYAN; SAIDAH, HUMAIRO; SAADI, YUSRON; SULISTIYONO, HERI; RAI K W, I G AGUNG NGURAH (GANEC SWARA, 2023)
The aim of this study is to determine the discharge of rainwater runoff from different durations of rain, to determine the magnitude of the differences in the discharge of rainwater runoff produced, and to determine the differences in channel dimensions resulting from differences in the duration of rain used. This study uses 6 years of daily rainfall data recorded at Bengel Station, to calculate the planned flood discharge as an alternative for controlling rain runoff in the Green Asia Housing area with a land area of ±6 hectares, a test time was used with rain times selected as 24 hours and 5 hours. Flood discharge is calculated using the Rational formula with a rain return period of 2 years according to the design area. The results of data analysis will be presented in the form of tables, discussed and concluded descriptively.The results of the study show that there is indeed a quite large difference in flood discharge, where the use of a 24-hour rain period produces a planned discharge that is around 32% lower than the use of a 5-hour rain period. The dimensions of the channel produced for a discharge with a rain duration of 24 hours are also smaller than the dimensions produced by a flow discharge with a rain duration of 5 hours. The fact is that rain events with a duration of shorter than 24 hours are more common than rain events lasting a full day.